STop OVarian CAncer (STOPOVCA) young: Protocol for a multicenter follow-up study to determine the long-term effects of opportunistic salpingectomy on age at menopause. (May 2022) - Gelderblom, Malou E.; IntHout, Joanna; Hermens, Rosella P.M.G; Coppus, Sjors F.P.J.; Ebisch, Inge; van Ginkel, Alexandra A.; van de Laar, Rafli; de Lange, Natascha; Maassen, Marloes; Pijlman, Brenda; Smedts, Huberdina P.M.; Vos, M. Caroline; et al.
Highlights: Opportunistic salpingectomy is a prophylactic method against ovarian cancer. Opportunistic salpingectomy may potentially damage the (micro)blood circulation to the ovaries. Damage to the blood circulation of the ovaries may lead to earlier onset of menopause. Studies of the effects of opportunistic salpingectomy on the onset of menopause are needed. The protocol of a prospective study to determine the long-term effects of opportunistic salpingectomy on age at menopause is presented. Abstract: Background: Opportunistic salpingectomy comprises additional bilateral salpingectomy during abdominal surgery as a prophylactic method to reduce the risk of ovarian cancer. However, opportunistic salpingectomy may potentially damage (micro)blood circulation to the ovaries, resulting in earlier onset of menopause. Primary objective: To evaluate the long-term effects of opportunistic salpingectomy on the onset of menopause in women who underwent sterilization through salpingectomy compared with a control group who underwent sterilization by tubal ligation or no surgery at all. Study hypothesis: Opportunistic salpingectomy does not lower the mean age at onset of menopause. Trial design: In a multicenter observational noninferiority study, we will prospectively compare the age at menopause of women initially aged 35–45 who underwent sterilization through opportunistic salpingectomy with a similarly aged control group who underwent sterilization by tubal ligation or no sterilization. Participants will be asked to complete an annual questionnaire on onset of menopause to eventually determine whether there is more than a one-year decrease in mean age at onset of menopause in the opportunistic salpingectomy group. Follow-up will last until determination of menopause, with a maximum of 15 years. Major inclusion/exclusion criteria: Inclusion criteria: pre-menopausal; age between 35 and 45; intact ovaries. Exclusion criteria: post-menopausal; previous bilateral salpingectomy or oophorectomy; previous hysterectomy; abnormal karyotype; previous or current chemotherapy or pelvic radiation. Primary endpoint(s): Determination of age of menopause measured by annual questionnaire. Sample size: 1200 (400 intervention group; 800 control group). Estimated dates for completing accrual and presenting results: It is estimated that recruitment will be completed by 2023 and results will be published by 2039. ClinicalTrials.gov identifier: : NCT04757922 Protocol version: : Version 1, February 2021